Study of the elderly females' voice by phonetography - Teles-Magalhaes, L. C.; Pegoraro-Krook, M. I.; Pegoraro, Renê [UNESP] (Singular Publishing Group Inc, 2000)
This study was carried out to investigate the voice characteristics of 40 healthy females with no voice disorders, ranging in age from 60 to 84 years ((X) over bar = 68.2 +/- 5.74 years). Measurements over all the entire phonational range were obtained by phonetography. The subjects were asked to sustain the vowel /a/ in modal register for a minimum of 5 seconds in the highest and lowest intensities after hearing the semitones C, E, G, and A, over all phonational ranges. The results indicated expansion of the low and reduction of high ends of the pitch range, decrease of the pitch numbers of the vocal range, restriction of the lowest and highest limits of the intensity, and reduction of either the maximum phonational range and the phonetogram area. The phonetography technique has shown efficacy to investigate the voice characteristics of elderly females.
Keywords: elderly voice; phonetography; vocal range profile